164 Better Together: Community Engagement During COVID-19. (April 2022) - Kraschnewski, Jennifer; Murray, Andrea
Abstract : OBJECTIVES/GOALS: The Penn State CTSI has been working diligently to help communities in their fight against COVID-19. As the rapidly evolving COVID-19 situation has unfolded the Penn State CTSI has been able to provide support to our community stakeholders. As our communities have and are faced with unprecedented challenges, our CTSI has been there every step of the way. METHODS/STUDY POPULATION: The Penn State CTSI is unique as it sits in rural Pennsylvania that not only spans a wide catchment area but also many diverse communities. The Penn State CTSI connected with our communities throughout the pandemic to bring timely and culturally appropriate information about the novel COVID-19 pandemic through our own institution and in partnership with community leaders. Stakeholder boards were formed to hear from various communities about hardships and challenges that were and are being faced due to COVID-19. RESULTS/ANTICIPATED RESULTS: The Penn State CTSI provided our communities with information through various different platforms to ensure that needs were being met in dissemination of pertinent information related to COVID-19. No only was information tailored to the specific needs that were discussed during stakeholder boards, the information was provided in different languages and platforms in order to meet cultural and other needs to ensure health equity and literacy were met. DISCUSSION/SIGNIFICANCE: Not only did the Penn State CTSI provide these services to our current community partners new partnerships were formed to create stronger alliances amongst those being serve. Members of the Penn State CTSI were invited to serve on state and local advisory bords and became trusted messengers in our communities.